Tissue-Specific Mitochondrial Decoding of Cytoplasmic Ca2+ Signals Is Controlled by the Stoichiometry of MICU1/2 and MCU - Melanie Paillard; György Csordás; Gergö Szanda; Tünde Golenár; Valentina Debattisti; Adam Bartok; Nadan Wang; Cynthia Moffat; Erin L. Seifert; András Spät; György Hajnóczky (Cell Reports, 2017)
Mitochondrial Ca2+ uptake through the Ca2+ uniporter supports cell functions, including oxidative metabolism, while meeting tissue-specific calcium signaling patterns and energy needs. The molecular mechanisms underlying tissue-specific control of the uniporter are unknown. Here, we investigated a possible role for tissue-specific stoichiometry between the Ca2+-sensing regulators (MICUs) and pore unit (MCU) of the uniporter. Low MICU1:MCU protein ratio lowered the [Ca2+] threshold for Ca2+ uptake and activation of oxidative metabolism but decreased the cooperativity of uniporter activation in heart and skeletal muscle compared to liver. In MICU1-overexpressing cells, MICU1 was pulled down by MCU proportionally to MICU1 overexpression, suggesting that MICU1:MCU protein ratio directly reflected their association. Overexpressing MICU1 in the heart increased MICU1:MCU ratio, leading to liver-like mitochondrial Ca2+ uptake phenotype and cardiac contractile dysfunction. Thus, the proportion of MICU1-free and MICU1-associated MCU controls these tissue-specific uniporter phenotypes and downstream Ca2+ tuning of oxidative metabolism.